(untitled) (Ágora de Heterodoxias, 2022)
We present an exercise in semiotic analysis, addressing the rhetorical codes (verbal, sound and visual tropes) of the advertising campaign of the Nike company, supported by the image of basketball player Michael Jordan to promote its brand of Air Jordan sneakers in audiovisual media between 1985 and 2020. The languages ​​used in the campaign to create consubstantial codes of recognition with culture and communication are studied, as advocated by the philosopher Umberto Eco. Semiotic communication and its metalanguages ​​are based on iconic signs and their combination with verbal and sound messages. The technique was documentary review. The information was recorded in files. The recognition codes in the verbal, sound and visual registers that have more presence in the analyzed messages are based on tropes such as hyperbole, asyndeton, synecdoche, reiteration and the figure of Michael Jordan as the antonomasia of basketball and success in business.